2018
DOI: 10.1515/cipms-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity-guided isolation of alkamides from a cytotoxic fraction of the ethyl acetate extract of Anacyclus pyrethrum (L.) DC. roots.

Abstract: Introduction. The alcohol extract of Pellitory (Anacyclus pyrethrum) roots has been previously shown to exert anticancer activities on the Human Colorectal Cancer Cell Line (HCT) by targeting apoptosis, metastasis and cell cycle arrest. However, the nature of the cytotoxic molecules associated with this activity remains unexplored. Aims. This study aims to reinvestigate Pellitory root extract as regard to its cytotoxic activity and to proceed to a bioguided fractionation to explore its active fraction and to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…According to a recent study, the ethyl acetate extract used to test the toxicity of the granulated roots showed LC50 = 249.3 gram per milliliters. Four alkamides, including pellitorine, are extracted during the fractionation test of this active extract; this impact may be attributed to their existence as this number is regarded as "toxic" [82].…”
Section: Toxicological Evidencementioning
confidence: 99%
“…According to a recent study, the ethyl acetate extract used to test the toxicity of the granulated roots showed LC50 = 249.3 gram per milliliters. Four alkamides, including pellitorine, are extracted during the fractionation test of this active extract; this impact may be attributed to their existence as this number is regarded as "toxic" [82].…”
Section: Toxicological Evidencementioning
confidence: 99%
“…As a result, the need for a practical and reliable method is evident, and this is where the A. salina assay stands out, allowing regular screening of the toxicity of natural compounds. Additionally, it is worth emphasizing that the National Cancer Institute (NCI) has established a significant association between the A. salina assay and the "in vitro" growth inhibition of human tumor cell lines (SILVA et al, 2007;HAMIMED et al, 2018).…”
Section: Correlation Between Toxicity Bioassay Using a Salina And Oth...mentioning
confidence: 99%
“…A recent study suggested that the assessment of toxicity is determined mainly in the ethyl acetate extract of the granulated roots, which showed LC 50 = 249.3 μg/mL. This value is considered “toxic”, therefore, the fractionation assay of this active extract leads to the isolation of four alkamides, including pellitorin, and this effect may be associated with their presence [ 100 ].…”
Section: Toxicological Evidencementioning
confidence: 99%